MENGISI KESENGGANGAN RUANG RISET AKUNTANSI DAN AUDITING MELALUI PARADIGMA INTERPRETIF DENGAN TEORI SOSIOLOGI - Ida Ayu Budhananda Munidewi; Nyoman Angga Pradipa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This paper is a form of concern for accounting research which is assessed by the author subjectively as only 'merely' fulfilling various existing criteria as an administrative requirement in filling the workload. However, there are also many who really devote their thoughts to seeing a phenomenon and reality about accounting that is happening around them. Qualitative research, especially interpretive research is seen as more suitable for finding meaning from an existing reality. Even accounting and social sciences are currently seen as unable to stand alone when photographing the reality in accounting, there is a need for harmony between accounting science and social theories that can generally be used in interpretive research to derive meaning and uniqueness from the interpretive paradigm. this is the involvement of researchers with the subjects studied. The development of the interpretive paradigm used in accounting and auditing research is seen from the publication of articles with this paradigm in reputable national journals (Sinta 2). This paper explores research that uses an interpretive paradigm, so that it can see future opportunities from interpretive research using social theories that can be more diverse. This paper uses a literature review that can provide an overview of the wider scope of accounting and auditing research using social theories in the interpretive paradigm.